Guidelines for the diagnosis and treatment of vitiligo in Japan. Issue 5 (27th February 2013) - Oiso, Naoki; Suzuki, Tamio; Wataya‐kaneda, Mari; Tanemura, Atsushi; Tanioka, Miki; Fujimoto, Tomoko; Fukai, Kazuyoshi; Kawakami, Tamihiro; Tsukamoto, Katsuhiko; Yamaguchi, Yuji; Sano, Shigetoshi; Mitsuhashi, Yoshihiko; et al.
Abstract Vitiligo is an acquired pigment disorder in which depigmented macules result from the loss of melanocytes from the involved regions of skin and hair. The color dissimilarity on the cosmetically sensitive regions frequently induces quality of life impairment and high willingness to pay for treatment in patients with vitiligo. The Vitiligo Japanese Task Force was organized to overcome this situation and to cooperate with the Vitiligo Global Issues Consensus Conference. This guideline for the diagnosis and treatment of vitiligo in Japan is proposed to improve the circumstances of Japanese individuals with vitiligo. Its contents include information regarding the diagnosis, pathogenesis, evaluation of disease severity and effectiveness of treatment, and evidence‐based recommendations for the treatment of vitiligo. The therapeutic algorithm based on the proposed recommendation is designed to cure and improve the affected lesions and quality of life of individuals with vitiligo.